Assessing antibiotics consumption, use and outcomes in a Yemeni tertiary hospital: A prospective cross-sectional study - Adel Ahmed Alshaikh; Mohammed Abdullah Kubas (PLoS ONE, 2025)
Background Antibiotics (ABs) have saved countless lives, but their misuse has led to a serious problem: antibiotic resistance. This growing phenomenon poses serious threats to public health worldwide, as it could make treating infections significantly more difficult in the future. Objectives This study aimed to investigate antibiotic consumption and use patterns in a tertiary hospital in Sana’a, Yemen, by comparing Prescribed Daily Doses (PDD) to Defined Daily Doses (DDD), and identifying factors associated with antibiotic misuse and its impact on patient outcomes. Methods A prospective cross-sectional study was conducted among adult inpatients in a tertiary hospital in Sana’a, Yemen over two months (January 12 to March 11, 2024), involving 597 patients. Data on antibiotic prescriptions, patient demographics, and outcomes were collected. Results A high prevalence of antibiotic use was observed (92.5%), with a notable proportion of prescriptions from the “Watch” category (56.7%). Significant PDD-DDD deviations were common, encompassing both overuse (36.8%) and underuse (63.2%). Factors associated with antibiotic deviations included patient age (26–44 years), gender (female), and ward type (private). The most commonly prescribed antibiotics were Ceftriaxone (33.6%), Metronidazole (21.8%), Vancomycin (6.0%), Levofloxacin (4.9%), Imipenem/Cilastatin (4.7%), and Moxifloxacin (3.6%). Notable deviations from DDD were observed for Levofloxacin (overuse by 28%), Imipenem/Cilastatin (underuse by 40.5%), and other agents. Antibiotic misuse was associated with longer hospital stays and less favorable discharge outcomes. Conclusion The study found an alarmingly high prevalence of antibiotic use and excessive consumption, with both overuse and underuse patterns observed, underscoring the need for effective regulatory interventions and improved antibiotic stewardship in Yemen.